Communication Strategies for Human-Elephant Conflict Mitigation in Tesso Nilo National Park: Multi-Stakeholder Approach - Malta, Refda Fachriza; Agustin , Herlina; Gumilar, Gumgum (KOMUNIKA, 2025)
Human-elephant conflict in Tesso Nilo National Park (TNTN) seriously challenged wildlife conservation and ecosystem management. The Reduced habitat through deforestation and the expansion of oil palm plantations has increased negative interactions between communities and Sumatran elephants (Elephas maximus sumatranus), causing economic losses and threatening the sustainability of the species. Using a qualitative case study approach, this study analyzed communication strategies to mitigate human-elephant conflict. Data were collected through in-depth interviews, field observations, and document analysis from various stakeholders, including buffer village communities and governmental organizations. Research findings indicate that communication barriers, such as low policy transparency, a lack of socialization, and inadequate community involvement in the formulation of conservation policies, exacerbate the conflict. Using participatory communication theory, this study recommends strategies that incorporate multi-party dialogues, community-based education, and communication technology for conflict mitigation. The results of this study contribute to the development of more inclusive and sustainable conservation policies and can be adapted to manage human-wildlife conflicts in other protected areas.